Relationship of Family Support Towards Self-Management and Quality of Life of Patients with Type 2 Diabetes Mellitus - Ahmad Yamin; Citra Windani Mambang Sari (Faculty of Nursing Universitas Padjadjaran, 2018)
DM disease will be suffered for life, so the patient is expected to establish self-management behavior in managing the disease. Self-management behavior in patient tends to decline with increasing complications perceived by patients. The presence of social support one of important factors to improve adherence of self-management Diabetes patients. The purpose of this study was to assess the relationship of social support towards self-management and the quality of life in DM patients in Bandung. This research used correlational approach with purposive technique sampling. Numbers of respondent were taken from the region of 10 Puskesmas with highest DM in Bandung on 92 patients who came to Puskesmas. The questionnaires used were Hensarling Diabetes Family Support Scale (HDFSS), Summary of Diabetes Self-management Activities Measure (SDSCA) and SF-36. The analysis used analysis using frequency distribution, and Spearman-rho. Most respondents (51.1%) had social support below the group median. Most respondents (50%) had a quality of life below the group median. Most respondents (52.2%) had DM self-management behavior below the group median. Bivariate results showed no relationship between social support support and self-management and quality of life of respondents (p value = 0.801). There is no significant relationship between social support and self-management and quality of life. Therefore, the studies are expected to be recommendations of this study was integrate nursing care to improve self-management and quality of life of DM patients.